Risk factors for cardiovascular diseases in adolescents - de Araújo Rodrigues, Naira Lígia; de Oliveira Lima, Luisa Helena; de Sousa Carvalho, Elaine; de Sousa Vera, Paula Valentina; de Macêdo Gonçalves Frota, Karoline; de Oliveira Lopes, Marcos Venícios; Araújo Rodrigues Oliveira, Edina (Investigación y Educación en Enfermería, 2015)
Objective. Identify risk factors for cardiovascular disease in adolescents. Methodology. Descriptive cross-sectional study, conducted from May to September 2012, in the public schools of the city of Picos (Piaui State, Brazil). The sample consisted of 320 adolescents 10-19 years. Results. As to gender, 60% were female. With regard to blood pressure values, 15.3% of participants had altered blood pressure values (6.9% with hypertension) and, in relation to nutritional status, 15.6% were overweight and 5.3% obese. None of the variables showed statistically significant differences according to sex. Correlation were found between the variables: family history of hypertension with arm circumference and triceps skinfold; maternal education with triceps skinfold thickness and diastolic blood pressure; uptime with body mass index, arm circumference, waist-hip ratio and heart rate; birth weight with body mass index and arm circumference. Conclusion. A significant proportion of adolescent respondents had risk factors for cardiovascular disease. Nursing should lead the adoption of interventions that promote the improvement of healthy lifestyle in adolescence, thus avoiding not only cardiovascular disease, but also other chronic diseases that can develop. How to cite this article: Rodrigues NLA, Lima LHO, Carvalho ES, Vera PVS, Frota KMG, Lopes MVO, et al. Risk factors for cardiovascular diseases in adolescents. Invest Educ Enferm. 2015; 33(2):